Analisis Financial Distress untuk Memprediksi Kebangkrutan dan Rasio Keuangan dalam Memprediksi Pertumbuhan Laba Pada Perusahaan (Studi Kasus Pada Perusahaan Kosmetik Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022) - Simamora, Ita Rahayu; Mahmudi, Abdul Halim; Yuwono, Minto (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
This research aims to investigate the impact of financial distress on predicting the potential for bankruptcy and investigate the influence of financial ratios in predicting profit growth in cosmetic companies listed on the Indonesia Stock Exchange during the period 2020-2022. This research uses a quantitative analysis approach to evaluate the level of financial health of companies, with a focus on identifying indicators of financial distress that may affect the financial conditions of cosmetic companies listed on the Indonesia Stock Exchange. Researchers use bankruptcy models and financial ratio analysis to measure the level of financial distress and predict company profit growth of the companies. This research uses data obtained from the financial reports of each company during the specified period from 2020 to 2022.